2020
DOI: 10.1371/journal.pone.0231136
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) severity on cellular bioenergetic function

Abstract: Myalgic encephalomyelitis/ Chronic fatigue syndrome (ME/CFS) has been associated with abnormalities in mitochondrial function. In this study we have analysed previous bioenergetics data in peripheral blood mononuclear cells (PBMCs) using new techniques in order to further elucidate differences between ME/CFS and healthy control cohorts. We stratified our ME/CFS cohort into two individual cohorts representing moderately and severely affected patients in order to determine if disease severity is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…These open-label studies need further follow-up; however, together with the present study and the previous metabolomics and proteomic studies of independent ME/CFS cohorts, they support dysregulated mitochondrial metabolism as an important feature of ME/CFS pathology. To some degree, abnormalities in bioenergetics parameters of blood cells have shown to correlate with the severity of ME/CFS symptoms [31,76]. Similarly, coupling efficiency correlated with symptom severity and disease duration in our cohort of ME/CFS patients.…”
Section: Discussionsupporting
confidence: 64%
“…These open-label studies need further follow-up; however, together with the present study and the previous metabolomics and proteomic studies of independent ME/CFS cohorts, they support dysregulated mitochondrial metabolism as an important feature of ME/CFS pathology. To some degree, abnormalities in bioenergetics parameters of blood cells have shown to correlate with the severity of ME/CFS symptoms [31,76]. Similarly, coupling efficiency correlated with symptom severity and disease duration in our cohort of ME/CFS patients.…”
Section: Discussionsupporting
confidence: 64%
“…Impaired Energy Metabolism in ME/CFS. Metabolomic studies have reported evidence of impaired ATP production from oxygen, glucose, fatty acids, and amino acids in multiple cell types (41,42,(91)(92)(93)(94). Not just oxidative phosphorylation but also glycolysisand possibly, the citric acid and urea cycles-are incriminated.…”
Section: Impaired Energy Metabolism In Covid-19 and Me/cfsmentioning
confidence: 99%
“…• Glucose via the tricarboxylic acid (TCA) cycle [96], reduced levels of fatty acids and of acyl-carnitine [97], and reduced levels of amino acids via the urea cycle [96,98]. • Impaired oxidative phosphorylation [99,100].…”
Section: Metabolomic Abnormalities In Me/cfsmentioning
confidence: 99%